Impacts of secure attachment, 5 factor personality, future time perspective on productive ageing - Rie, JuIl (Korean Journal of Industrial and Organizational Psychology, 2013)
It is hope and need of society that most of people will keep their life productive after becoming elderly. In this study, we want to find demographic-sociological and psychological determinants for productive ageing. In our study, productive ageing were constructed as 4 factors, goal pursuit activities, career development activities, family support activities, and society volunteering activities. We collected data from 471 elderly beyond 65. Sex, age, spouse existence, income by month, education, work or non-work, working time were correlated significantly with productive ageing. And openness to experience and conscientious personality, secure attachment, and future time perspective were correlated significantly with productive ageing. Especially, big five personality and future time perspective impacted significantly on productive ageing after controling demographic-sociological factors through hierarchical regression analysis. Openness to experience and future time perspective were important consistently for all productive ageing activities. When we analyzed causal relationship among openness to experience, secure attachment, future time perspective and productive ageing through AMOS, future time perspective mediated relationship between openness to experience and productive ageing, and relationship between secure attachment and productive ageing. Also, openness to experience, secure attachment, and time perspective all had a big impact on productive ageing directly.